Peranan Bhabinkamtibmas terhadap Penanganan Produksi Sopi di Desa Fat, Nusa Tenggara Timur - Jener Blasius; Suheflihusnaini Ashady (Juridische : Jurnal Penelitian Hukum, 2024)
Sopi is a traditional drink that contains alcohol. Its existence raises pros and cons among the people of East Nusa Tenggara. Sociologically, Sopi is considered to have certain values that are respected by the local community, but if consumed excessively, the alcohol content contained can also be the cause of criminal acts. In this research, the author conducted a sociological study of the existence of Sopi in Fat village, East Nusa Tenggara and the role of Bhabinkamtibmas in efforts to handle Sopi production. The research results show that social, cultural and economic problems are very complex factors that are always considered in relation to the existence of sopi in society